Pitting Corrosion Investigation of Cantilever Beams Using F. E. Method - Nagler, Jacob (My University, 2013)
Carbon steel cantilever beams are widely used in many applications in aerospace, civil and mechanical engineering. Pitting corrosion is a phenomenon which places severe limitations on the design of such applications. As such, understanding this phenomenon and the methods to deal with it, are of a great importance. This paper presents numerical investigation by using F. E. (Finite Element) simulation on the load carrying capacity of corroded cantilever beams with pitting corrosion damage. The pitting corrosion hole shape has been modeled using ASTM G46 Standard Guide. Several different cases of pitting corrosion, represented by hemispherical holes, were modeled and examined by using ANSYS computer program. Clamped edge constraint was used on one end, while the other end was free. In these F. E. models, element of Solid95 was used and comparison to Bernoulli-Euler theory was made. The effect of the radius of the pitting corrosion holes on the stresses in the beam was examined in comparison to yield stress. It has been found that the M. S. (Margin of Safety) has been reduced gradually with increasing radii. Agreement with Bernoulli-Euler theory has been achieved only for small radii. Moreover, three methods of pitting corrosion repairs were examined, together with Bernoulli-Euler theory comparison: 1) Regular surface repair; 2) Extension surface repair; and 3) “Handy Removal”. It was found that extension surface repair has the highest M. S. value
Keywords: Pitting Corrosion; Carbon Steel; Bernoulli Euler; Simulation